Success and Constraints of LEEMP Community Development Projection in Benue State, Nigeria - Ochepo, C. O.; Okwoche, V. A.; Alfa, G. B. (Advances in Social Sciences Research Journal, 2016)
The study was conducted to evaluate the success and constraints of local empowerment and environmental management project (LEEMP) community development project in Benue state, Nigeria. The study focused on the socio economic characteristics of the beneficiaries in the target communities, compare the standard of living of LEEMP communities before and after LEEMP project, and identify the constraints in the implementation of LEEMP. Primary information was collected from 225 beneficiaries through a multistage sampling technique. Primary data was used for the study which was garnered through a well structured questionnaire and interview sections with LEEMP beneficiaries. The socioeconomic characteristics of respondents were analyzed descriptively, impact of LEEMP on target communities where presented in a tabular form, while five point likert type scales was used to analyze the awareness and participation level respectively. It was found that education, income, sex and household size influenced respondents level of participation and subsequently the success of the project. LEEMP used a strategy that enabled community members to participate and established projects that were prioritized by them which led to national and community development, contributing greatly to improvement in the standard of living of the targeted rural communities.